Pemberdayaan Perempuan Pesisir Madura: Studi Kasus pada Industri Rumput Laut dan Olahan Hasil Laut di Pulau Poteran Sumenep - Erfan Erfan; Eny Haryati; Aris Sunarya; Ika Devy Pramudiana (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Coastal women on Poteran Island, Sumenep, have an important role in the marine-based economic sector, especially in the seaweed and processed seafood industry. However, limited access to capital, technology, and markets are the main challenges in their empowerment efforts. This study aims to analyze the level of empowerment of coastal women in the industry and identify factors that support and hinder the development of their businesses. This study uses a qualitative method with a case study approach, where data is collected through in-depth interviews with women entrepreneurs, participant observation, and related literature studies. Data analysis techniques are carried out through the Miles and Huberman interactive model which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the empowerment of coastal women in the seaweed and processed seafood industry has had a positive impact on family economic welfare, increased skills capacity, and strengthened their social roles in the community. However, there are still obstacles in terms of market access, policy support, and production technology that need further attention. Therefore, intervention from various stakeholders is needed to increase women's access to skills training, business capital, and policies that support the sustainability of their businesses.